WHAT MAKES HUMAN RESOURCE PROFESSIONALS USE ARTIFICIAL INTELLIGENCE FOR REDESIGNING JOBS: A UTAUT2 STUDY - Eftimov, Lјupcho; Kitanovikj, Bojan (Varazdin Development and Entrepreneurship Agency, Varazdin, Croatia / University North, Koprivnica, Croatia / Faculty of Management University of Warsaw, Warsaw, Poland / Faculty of Law, Economics and Social Sciences Sale - Mohammed V University in Rabat, Morocco / ENCGT - Ecole Nationale de Commerce et de Gestion de Tanger - Abdelmalek Essaadi University, Tangier, Morocco / Polytechnic of Medimurje in Cakovec, Cakovec, Croatia, 2024)
As artificial intelligence (AI) found new applications in human resource (HR) practices in recent years due to its increasing accessibility, HR professionals question to which extent and where can this technology help them become more efficient and productive. Even though AI is not something new to HR functions like recruitment and selection, performance management, or training and development, not much is known about the use of this technology for efficiently redesigning jobs for the modern age. As a result, this study’s objective is to assess the factors that shape the behavioural intentions of employees in HR departments to utilize AI explicitly for job redesign. The authors employ a multiple linear regression method, based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) theoretical model and data from a sample of 107 HR professionals. The findings from the study can potentially have practical implications for policymakers, who are still focused on developing suitable AI regulation, as well as HR managers and business leaders in the organizational context. In this sense, the findings can help them craft strategies for using AI to redesign existing jobs effectively and ethically as well as point out the main facilitating conditions and factors that can ultimately change behaviours. After a thorough query of the Scopus database, it was concluded that this would be one of the first studies that delve into the application of AI for job redesign, which represents an additional motivation for the authors to conduct the research.
Keywords: Artificial intelligence, Human resource management, Job redesign, UTAUT2